Covalent incorporation of the surfactant into high internal phase emulsion templated polymeric foams1. Issue 36 (4th May 2015) - Kovačič, Sebastijan; Preishuber-Pflügl, Florian; Pahovnik, David; Žagar, Ema; Slugovc, Christian
<x xml:space="preserve">Abstract</x> This paper describes a "one pot" approach where intrinsically hydrophobic polymer foams are turned more hydrophilic by covalent incorporation of the surfactant.